2001
DOI: 10.1016/s0006-3495(01)75916-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Membrane Reorganization Induced by Chemical Recognition

Abstract: Nanoscale structural reorganization of a lipid bilayer membrane induced by a chemical recognition event has been imaged using in situ atomic force microscopy (AFM). Supported lipid bilayers, composed of distearylphosphatidylcholine (DSPC) and a synthetic lipid functionalized with a Cu(2+) receptor, phase-separate into nanoscale domains that are distinguishable by the 9 A height difference between the two molecules. Upon binding of Cu(2+) the electrostatic nature of the receptor changes, causing a dispersion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…We note that the TIRFM and AFM data sets are not perfectly correlated. This is likely a consequence of a nonuniform distribution of the GT 1 B receptor in the fluid phase of the supported bilayer and hence, the distribution of the FITC-Tet C molecules bound to G T1b (49,50). We also cannot discount the possibility that the dynamics of the lipid bilayer may be better resolved on TIRFM timescales rather than on AFM imaging timescales (33).…”
Section: Figurementioning
confidence: 93%
“…We note that the TIRFM and AFM data sets are not perfectly correlated. This is likely a consequence of a nonuniform distribution of the GT 1 B receptor in the fluid phase of the supported bilayer and hence, the distribution of the FITC-Tet C molecules bound to G T1b (49,50). We also cannot discount the possibility that the dynamics of the lipid bilayer may be better resolved on TIRFM timescales rather than on AFM imaging timescales (33).…”
Section: Figurementioning
confidence: 93%
“…Complete reversibility was shown by removal of the metal ions with ethylenediaminetetraacetic acid (EDTA). This strategy has been successfully demonstrated with iminodiacetic acid 1 as a receptor for Cu 2+ and Fe 3+ , with dithioamide 2 for Hg 2+ , and with [18]crown‐6 3 for Pb 2+ . Notably, the authors found that the binding affinity of the iminodiacetic acid head group in 1 with various metal cations in vesicles paralleled the affinity in solution, albeit reduced by a factor of 100–1000 …”
Section: Membrane‐based Sensingmentioning
confidence: 99%
“…The same group of researchers had earlier imaged, using the in situ AFM, a nanoscale structured reorganization of a lipid bilayer membrane composed of distearyl phosphatidyl choline (DSPC) and a synthetic lipid functionalized with a Cu 2+ receptor (pyrenenoyl steryl-glycero-imidodiacetic acid) upon binding Cu 2+ . The observed dispersion of the receptor molecules in the membrane was reversible through the removal of metal ions with EDTA [48]. The in situ recognition of hydrogen bonding [49], avidin-biotin pairs [50], antibody-antigen pairs [51] and DNA strands [52] with AFM by probe-surface adhesion measurements and topography imagery has been shown to be a powerful tool to locate specific molecular interaction with a sensitivity to single molecular bonding forces.…”
Section: Modeling Of Cellular Membrane Recognition Eventsmentioning
confidence: 99%